Evaluation of Protective Effect of Methyl Sulfonyl Methane on Colon Ulcer Induced by Alendronate - Safaa William Mdawar; Shaza Anwar Al Laham; Ahmad Izzat Al-Manadili (Journal of Pharmacy and Nutrition Sciences, 2017)
Background: Bisphosphonates represent a new class of drugs that have shown very promising therapeutic efﬁcacy in the treatment of a number of diseases associated with abnormally accelerated bone resorption including osteoporosis, Paget’s disease, and hypercalcemia of malignancy. As an increasing number of these drugs become available for clinical use in the treatment of the millions of individuals with these skeletal diseases, evidence is becoming available that their chronic usage may be associated with a number of gastrointestinal side effects, such as diarrhea, abdominal pain and inﬂammation, and erosions and ulceration of the upper gastrointestinal tract. Methyl sulfonyl methane (MSM) which is used for osteoarthritis was used to prevent bisphosphonates ulceration. Our objective was to study the preventive effect of MSM against colon ulcer induced by Alendronate (ALN) in rats. The experiments had been done on 8 white wistar rats for each group. The gastric ulcer has been induced by administration of Alendronate (20mg/kg/day) by gavage for 4 days. MSM (400mg/kg/day) has been given for the protective group for 4 days before administration of Alendronate. The ulcers in rats' colon were examined histologically and microscopically. The results showed that administration of MSM before Alendronate inducing ulcer led to a reduction in ulceration and showed significant difference comparing with morbidity group. Conclusion: MSM (400 mg/kg/day) has protective effect of colon ulcer induced by alendronate.